Optimal harvesting duration for CDMA systems. (17th December 2021) - Touati, Sami; Sammouda, Rachid; Alhussein, Musaed A.
This paper studies the throughput of code division multiple access (CDMA) systems with energy harvesting using the received radio frequency (RF) signal at the transmitter. A CDMA transmitter T harvests energy using the received signals from node N . Then, the harvested energy is used to transmit data to a CDMA receiver R . We derive the throughput at the receiver as well as the cumulative distribution function (CDF) of signal to noise ratio (SNR). We also suggest to optimise harvesting duration to maximise the throughput. The proposed optimal harvesting duration allows to double the throughput at high SNR with respect to a network where harvesting and data transmission phases have the same durations. CDMA systems with energy harvesting do not require to recharge or change the battery of transmitter T . Our results are valid for any number of paths between N and T and any number of paths between T and R .